Revealing the role of HBr in propane dehydrogenation on CeO2(111) via DFT-based microkinetic simulation. Issue 16 (12th April 2022) - Jan, Faheem; Lian, Zan; Zhi, Shuaike; Yang, Min; Si, Chaowei; Li, Bo
Abstract : HBr triggered the activities of catalytic propane dehydrogenation with balanced stability and selectivity. Abstract : HBr, as a soft oxidant, has been demonstrated to have a good balance between stability and selectivity in catalytic propane dehydrogenation. However, the origin of enhancements induced by HBr (hydrobromic acid) remains elusive. In this study, DFT-based microkinetic simulations were performed to reveal the reaction pathway and performance of propane dehydrogenation catalyzed by CeO2 in the presence of HBr. Three scenarios were under the investigations, which are pristine, dissociated HBr, and Br assisted surface hydroxyl. The calculations indicated that HBr significantly enhanced the adsorption of propane and provided alternative pathways for propene formation. More significantly, the energy barrier of C–H bond activation in propane was reduced with the assistance of HBr. It was very interesting to find that the reactivity of surface hydroxyl remarkably increased for C–H bond activation in the presence of HBr. The positive role of HBr is clearly evident from the microkinetic simulation. The TOFs of both propane conversion and propene formation increased after the introduction of HBr, which correlates with the apparent decreased activation energy. The reaction rate has a first order dependence on C3 H8 and zero order dependence on HBr. The current study lays out a solid basis for further optimization of the performance of propane dehydrogenation.